Truffle trouble [large type] - Flower, Amanda (Flower, Amanda. Amish candy shop mystery, 2026)
"Summer is finally upon the village of Harvest, Ohio, nestled in picturesque Amish Country, and folks are abuzz over their very own Bailey King's upcoming June wedding. The Amish candy shop owner and star of TV's Bailey's Amish Sweets is marrying Holmes County Sheriff Aiden Brody. To sweeten the occasion will be a scrumptious giant chocolate truffle wedding cake, made especially for the happy couple by Bailey's New York City mentor, Jean Pierre. Other than the risk of the ring bearer, Jethro the pig, taking a bite out of the confection, what could go wrong? As it turns out, a food-related disaster does befall the day. But with Bailey in the mix, it's nothing so pedestrian as a peckish pig. At the reception, a wedding guest dies after sampling the hors d'oeuvres. Café owner and new caterer Darcy Woodin, who made all the food except the desserts, is pegged by police as the number one suspect. Even more incriminating, the victim is one of Darcy's ex-boyfriends . . . Still, Bailey is friends with Darcy, and she's certain the young woman is innocent. Even before the first dance with her new husband, Bailey's on the case. Can she help solve it in time for her honeymoon-or will a killer try to end her happily ever after before it's even begun?"--